Analisis Beban Listrik Saat Operasi Penangkapan Ikan Pada KM. Sumber Natuna - Mardiyono Mardiyono (Energi & Kelistrikan, 2020)
The use of electric load in km. Sumber Natuna against capacity generators on every operation condition good day as well as night is different – different. The results of usage of electric load at km. Sumber Natuna include lighting, installation of aircraft electrical and motor-electric motor, with the overall power of 187.567 Watt. Maximum electric load usage at night that is at the time of the arrest operation in Fishing Ground of 169,521 Watt with power effectiveness of 84.7% and during the day on the way back towards the harbour i.e. of 126,232 Watt with power effectiveness of 63.1%. The maintenance activity performed often plying consists of: an examination of the State of the generator visually, cleaning the outside of the generator, checks on excessive heat on the generator. To keep the generators as power plants on board can work optimally and not much experience constraints, then the generator must be supported by the activities of care of components that work well and planned.